Novel DBA Schemes for Improving Bandwidth Utilization and QoS in EPON System - Beybutyan, Davit V. (Mathematical Problems of Computer Science, 2021)
The paper proposes some advanced DBA schemes for the improvement of QoS in EPON systems, as well as for the improvement of system performance and bandwidth utilization. The proposed DBA schemes enable the feeder fibers to provide a recovery mechanism. It can also share the load of the feeder fiber works, if no failures occurred. When the failures occur on the OLT or feeder fibers, the backup fibers will recover the failed ones. The PFWBA scheme integrates an efficient DBA and EDBA mechanisms of PFEBA for improving the prediction accuracy and system performance. The paper is proposing new algorithms for DBA schemes to improve the P2P VoD services. The proposed DBA schemes also outperform the early proposed DBA schemes.